2007
DOI: 10.1161/circresaha.107.155531
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channel 6–Mediated, Localized Cytosolic [Na + ] Transients Drive Na + /Ca 2+ Exchanger–Mediated Ca 2+ Entry in Purinergically Stimulated Aorta Smooth Muscle Cells

Abstract: Abstract-The Na ϩ /Ca 2ϩ exchanger (NCX) is increasingly recognized as a physiological mediator of Ca 2ϩ influx and significantly contributes to salt-sensitive hypertension. We recently reported that Ca 2ϩ influx by the NCX (1) is the primary mechanism of Ca 2ϩ entry in purinergically stimulated rat aorta smooth muscle cells and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 53 publications
11
108
0
Order By: Relevance
“…5B). This is consistent with a functional linkage of ROCs to NCX1 and ␣ 2 -Na ϩ pumps in rodents (34,46,49).…”
Section: Expression Of Nasupporting
confidence: 86%
See 1 more Smart Citation
“…5B). This is consistent with a functional linkage of ROCs to NCX1 and ␣ 2 -Na ϩ pumps in rodents (34,46,49).…”
Section: Expression Of Nasupporting
confidence: 86%
“…These Na ϩ and Ca 2ϩ transporter protein distribution patterns are very similar to those in rodent arterial myocytes and some other cell types (26,31,39,46,48,54). The implication of this structural organization, consisting of units (plasmerosomes) of PM microdomains closely opposed to junctional SR, is that the ␣ 2 -Na ϩ pumps, NCX1 and ROCs (of which TRPC6 proteins are components), and the SR are also functionally linked (8).…”
Section: A B C D Esupporting
confidence: 58%
“…Here, we showed that human pancreatic cancer cells express TRPC1, 4, and 6 but not other isoforms. TRPC1 is believed to be a functional SOC in other cell types, including intestinal epithelial cells (38,48), and TRPC6 to be a functional receptor-operated channel (ROC) (34,45). Moreover, our data from the use of TRPC1 and NCX1 siRNAs strongly suggest coupling of TRPC1-encoded SOC and NCX1 in regulating human pancreatic cancer cell motility.…”
Section: Discussionmentioning
confidence: 74%
“…The direction of NCX-mediated Ca 2+ movement depends on membrane potential and/or cytosolic Na + or Ca 2+ concentration (3). During adrenergic and purinergic stimulations, Na + entry through NSCC has been shown to drive NCX-mediated Ca 2+ entry in vascular smooth muscle (4,5). In addition, the Ca 2+ entry mode of NCX has been proposed to contribute to the increased vascular tone in salt-sensitive hypertensive rats (6).…”
Section: /Camentioning
confidence: 99%